ENHANCING SUSTAINABLE STUDENTS' MOBILITY: A CASE STUDY OF THE UNIVERSITY OF ALGIERS - Sarra Achoura,; Imane Haraoubia,; Maria Inmaculada Mohino Sanz, (International Journal of Innovative Technologies in Social Science, 2024)
This study assesses student mobility’s sustainability at the University of Algiers, identifying barriers and evaluating the impact of mobility patterns and infrastructure. Through a mixed-methods approach, including surveys and interviews, the research explores the daily transportation challenges of students. Key findings highlight barriers to sustainable mobility, including long commute times, inadequate pedestrian infrastructure, and safety concerns. The study also underscores the limited accessibility of transportation services for individuals with disabilities and the poor physical condition of public transportation infrastructure. The analysis reveals that while public transportation is widely used, it fails to meet the demands of the students, with overcrowding, poor maintenance, and limited accessibility options impacting the quality of commutes. To promote sustainable mobility, the study recommends improvements in traffic management, pedestrian infrastructure, and the safety and reliability of transportation services. The findings help policymakers and university administrators to enhance the sustainability and accessibility of student mobility in Algiers.